THE APPLICATION OF SUMMARIZING TECHNIQUE TO IMPROVE STUDENTS' WRITING ABILITY - Tiwa, Jerikho Louis; Maru, Mister Gidion; Lolowang, Imelda S. (SoCul: International Journal of Research in Social Cultural Issues, 2024)
This study aims to determine the effectiveness of summarizing strategies in improving students’ writing ability. Students at SMA N 1 Lembean Timur continue to experience low writing proficiency, which is marked by limited English vocabulary and weak sentence construction skills. This quantitative study employed a pre-experimental design using a single-group pre-test and post-test format. Purposive sampling was used to select 20 out of 60 eleventh-grade students at SMA N 1 Lembean Timur as the research sample. The study was conducted over two weeks in May 2023. An expository writing test was used as the research instrument, requiring students to write a short expository paragraph that was evaluated based on content, organization, vocabulary, grammar, and mechanics. To determine the significance of the improvement, the data were analyzed using gain scores and a t-test. The results showed a significant improvement in students’ writing performance, with the mean pre-test score increasing from 57.50 to 74.00 in the post-test. A statistically significant difference was indicated by the significance value, which was less than 0.05 (p = 0.000 < 0.05). As a result, the null hypothesis (H₀) was rejected, and the alternative hypothesis (H₁) was accepted. These findings demonstrate that summarizing strategies effectively enhance students’ writing abilities and should be appropriately applied in classroom instruction to improve students’ learning outcomes.